FRI0704 Analysis of risk factor for pregnancy outcomes in 142 pregnancies complicated with connective tissue disease. (15th June 2017) - Shimada, H; Kanenishi, K; Kameda, T; Izumikawa, M; Nakashima, S; Ozaki, H; Wakiya, R; Kondo, A; Kadowaki, N; Dobashi, H
Abstract : Background: Recently, many connective tissue disease (CTD) patients wish to become a mother because immunosuppressants and biologics enable to improve the outcome of underlying CTD and quality of life respectively. However, Pregnancies in CTD patients often have problems including underlying disease exacerbation, some complications during pregnancy especially in preterm birth, light for date (LFD) and premature rapture of membrane (PROM). Previous study identified that high clinical activities with hypocomplementemia and positive anti-dsDNA antibody were at highest risk for pregnancy loss and preterm delivery in SLE 1) . It is unclear whether these problems are associated with the activity of underlying CTD or immunosuppressant treatment. Objectives: We examine the issue of pregnancy and delivery complicated with CTD by the analysis of the cases in our institution. Methods: We investigated the risk factors of preterm birth, LFD (light for dates) and perinatal complication from exacerbation of underlying disease, anti SS-A antibody, antiphospholipid antibody, doses of corticosteroid, immunosuppressants or biologics before pregnancy in 142 cases which were delivered in our institution. Results: In 23 among all cases underlying diseases were exacerbated, and these occurred more often in PM/DM (60%), MCTD (33.3%), RA (15.3%) and SLE (13.3%). In SLE, SS, MCTD and PM/DM, preterm births and LFD were closely related to disease exacerbation and dose of corticosteroid, pulse therapy, and these were extracted as risk factors for these perinatal complications. Preterm birth was also associated with low complement (CH50) and high titer of anti-dsDNA antibody, and LFD was associated with high titer of anti-dsDNA antibody before pregnancy. However, there was no significant association with these factors in threatened premature delivery and PROM. In RA, perinatal complications were not influenced by methotrexate and biologics before pregnancy. However, only LFD was related with doses of corticosteroid during pregnancy. Conclusions: We extracted disease exacerbation and dose of corticosteroid, pulse therapy during pregnancy and also low complement, high titer of anti-double stranded DNA antibody before pregnancy as risk factors of pregnancy outcomes. In pregnancy complicated with CTD, we need to control the disease activity strictly, however, we should consider the increase or pulse therapy of corticosteroid carefully. References: Clowse ME, Maqder LS, et al. The clinical utility of measuring complement and anti-dsDNA antibodies during pregnancy in patients with systemic lupus erythematosus. J Rheumatol. 2011 Jun; 38(6):1012–6. Disclosure of Interest: None declared